An experimental investigation on L9 orthogonal array with various concrete materials. (2021) - Sabarish, K.V.; Parvati, T.S.
Abstract: The principle extent of this task is to diminish the expense of material and furthermore decreases the work by utilizing Taguchi strategy for parameter structure. In this manuscript the beam structure is examined by various composite materials like Fly-ash, M−sand, Water-to-Cement ratio and Sisal fiber. The flexural test was conducted on 28th day and 60th day. Both conventional test and special test was examined with Taguchi Optimization method with L9 orthogonal array. And which was cross examined by Grey Relational Grade (GRG) method. The experimental data was analyzed using Analysis of variance (ANOVA).The response from all the methodology depicts the best optimal combination with minimal resource which highly limit the total duration of the project.